Barorezeptorakivierungstherapie bei therapierefraktärer Hypertonie: Indikation und Patientenselektion : Empfehlungen der BAT-Konsensusgruppe 2017 = Baroreceptor activation therapy for therapy-resistant hypertension : indications and patient selection : recommendations of the BAT consensus group 2017 - Koziolek, Michael Johann; Krämer, Bernhard (Der Internist, 2017)
Baroreceptor activation therapy (BAT) has been available for several years for treatment of therapy-refractory hypertension (trHTN). This procedure is currently being carried out in a limited number of centers in Germany, also with the aim of offering a high level of expertise through sufficient experience; however, a growing number of patients who are treated with BAT experience problems that treating physicians are confronted with in routine medical practice. In order to address these problems, a consensus conference was held with experts in the field of trHTN in November 2016, which summarizes the current evidence and experience as well as the problem areas in handling BAT patients.